Participation in a Public Insurance Program: Subsidies, Crowd-Out, and Adverse Selection - Stephen H. Long; M. Susan Marquis (SAGE Publishing, 2002)
This paper examines how varying the level of subsidies affects participation in a public insurance program, crowd-out of private insurance, and adverse selection. We study the experience in Washington's Basic Health program in 1997. Findings show that adverse selection is not a problem in voluntary public programs. Increasing subsidies have only modest effects on participation in subsidized programs, though the gains are not at the expense of the private market. Overall participation in the subsidized plan is also modest, even though participants benefit from it. The challenge to policymakers is to find program design characteristics, beyond subsidies, that attract the uninsured.